Exploring the mesoscale activity in the Solomon Sea: A complementary approach with a numerical model and altimetric data. Issue 4 (14th April 2014) - Gourdeau, L.; Verron, J.; Melet, A.; Kessler, W.; Marin, F.; Djath, B.
Abstract The Solomon Sea is an area of high level of eddy kinetic energy (EKE), and represents a transit area for the low‐latitude western boundary currents (LLWBCs) connecting the subtropics to the equatorial Pacific and playing a major role in ENSO dynamics. This study aims at documenting the surface mesoscale activity in the Solomon Sea for the first time. Our analysis is based on the joint analysis of altimetric data and outputs from a 1/12° model simulation. The highest surface EKE is observed in the northern part of the basin and extends southward to the central basin. An eddy tracking algorithm is used to document the characteristics and trajectories of coherent mesoscale vortices. Cyclonic eddies, generated in the south basin, are advected to the north by the LLWBCs before merging with stationary mesoscale structures present in the mean circulation. Anticyclonic eddies are less numerous. They are generated in the southeastern basin, propagate westward, reach the LLWBCs, and dissipate. The seasonal and interannual modulations of the mesoscale activity are well marked. At seasonal time scale, maximum (minimum) activity is in May–June (September). At interannual time scale, the mesoscale activity is particularly enhanced during La Niña conditions. If instabilities of the regional circulations seem to explain the generation of mesoscale features, the modulation of the mesoscale activity seems to be rather related with the intrusion at Solomon Strait of the surface South Equatorial Current, rather than to the LLWBCs, by modulating the horizontal and vertical shears suitable for instabilities.